Sustained-release solid dispersion of pelubiprofen using the blended mixture of aminoclay and pH independent polymers: preparation and in vitro/in vivo characterization - Yeo-Song Lee; Jae Guen Song; Sang Hoon Lee; Hyo-Kyung Han (Taylor & Francis Group, 2017)
The present study aimed to develop the sustained-release oral dosage form of pelubiprofen (PEL) by using the blended mixture of 3-aminopropyl functionalized-magnesium phyllosilicate (aminoclay) and pH-independent polymers. The sustained-release solid dispersion (SRSD) was prepared by the solvent evaporation method and the optimal composition of SRSD was determined as the weight ratio of drug: Eudragit® RL PO: Eudragit® RS PO of 1:1:2 in the presence of 1% of aminoclay (SRSD(F6)). The dissolution profiles of SRSD(F6) were examined at different pHs and in the simulated intestinal fluids. The drug release from SRSD(F6) was limited at pH 1.2 and gradually increased at pH 6.8, resulting in the best fit to Higuchi equation. The sustained drug release from SRSD(F6) was also maintained in simulated intestinal fluid at fasted-state (FaSSIF) and fed-state (FeSSIF). The structural characteristics of SRSD(F6) were examined by using powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FT-IR), indicating the change of drug crystallinity to an amorphous form. After oral administration in rats, SRSD(F6) exhibited the prolonged drug exposure in plasma. For both PEL and PEL-transOH (active metabolite), once a day dosing of SRSD(F6) achieved oral exposure (AUC) comparable to those from the multiple dosing (3 times a day) of untreated drug. In addition, the in vivo absorption of SRSD(F6) was well-correlated with the in vitro dissolution data, establishing a good level A in vitro/in vivo correlation. These results suggest that SRSD(F6) should be promising for the sustained-release of PEL, thereby reducing the dosing frequency.